2023
DOI: 10.3389/fpsyg.2023.1083520
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and academic procrastination in Chinese college students: The serial mediating roles of physical self-perceptions and self-esteem

Abstract: Studies have demonstrated that physical activity (PA) is negatively associated with academic procrastination. However, there is limited research on the mechanism underlying this relationship. This study aims to explore the relationship between PA and academic procrastination by investigating the roles of physical self-perceptions and self-esteem. 916 college students (650 females; Mean age = 19.11, SD age = 1.04) participated in the study. Participants completed the Physical Activity Rating Scale-3, the Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Furthermore, empirical studies of procrastination in life and education have revealed its far-reaching consequences. Ren et al (2023) found that procrastination is associated with lower academic performance, increased stress, and reduced well-being. Moreover, Shahri and Sayyedalhosseini (2021) demonstrated that procrastination could lead to short-term benefits, such as reduced stress and increased positive mood, but would eventually result in long-term costs, including heightened stress and reduced academic performance.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Furthermore, empirical studies of procrastination in life and education have revealed its far-reaching consequences. Ren et al (2023) found that procrastination is associated with lower academic performance, increased stress, and reduced well-being. Moreover, Shahri and Sayyedalhosseini (2021) demonstrated that procrastination could lead to short-term benefits, such as reduced stress and increased positive mood, but would eventually result in long-term costs, including heightened stress and reduced academic performance.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Some studies have confirmed the significant positive predictive effect of physical exercise on body self-esteem, indicating that regular physical training can elevate levels of body self-esteem, with higher levels of physical activity correlating with higher levels of body self-esteem ( 22 , 23 ). Furthermore, empirical research by Ren et al ( 24 ) has shown a significant negative correlation between body self-esteem and procrastination behavior. Based on these findings, this study hypothesizes that body self-esteem mediates the impact of physical activity on college students’ procrastination behavior (H2).…”
Section: Introductionmentioning
confidence: 99%
“…The article also suggests certain improvement strategies, such as enhancing the curriculum to provide individual exercise guidelines [13] , promoting proper dietary habits, offering psychological counseling, and establishing healthy lifestyle guidelines [14] . The study has some limitations, and future research could consider additional factors like the students' academic disciplines (e.g., STEM or humanities), their place of origin, and their lifestyle habits as influencing factors for analysis.…”
mentioning
confidence: 99%